Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas terhadap Earning Per Share pada Bank Umum yang Terdaftar di Bursa Efek Indonesia - Rizki Muhammad Siddiq; Setiawan Setiawan; Ade Ali Nurdin (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
In conducting this research which aims to find out from the influence of Loan to Deposit Ratio (LDR), Debt to Assets Ratio (DAR), and Return on Assets (ROA) to Earning per Share (EPS) in Commercial Banks listed on the IDX period 2008-2017. In this study the type of data used is secondary data, which is from financial statement data that has been published by the website on the Indonesia Stock Exchange and the website of each company that will be examined in the period 2008-2017. The total sample used in this study is four bank companies in the banking sub-sector that have been listed on the Indonesia Stock Exchange from 2008-2017. The technique that will be used in the way of sampling is by purposive sampling technique is a technique of determining samples with certain considerations. The analysis technique in this study uses panel data regression analysis using the Eviews 10 program tool.